Factors associated with food insecurity among the chronically ill population during the COVID-19 pandemic in the United States - Dean, Caress A.; Liu, Echu; Enard, Kimberly R.; Qian, Zhengmin; Elder, Keith T. (Frontiers in Public Health, 2023)
Little is known about food insecurity among Americans with chronic diseases, one of the vulnerable groups in health care. Factors influencing food insecurity among this population group are especially poorly understood. Using data from the COVID Impact Survey, this cross-sectional study sought to examine food insecurity among adults with chronic diseases in the United States and to identify factors associated with their risks for food insecurity during the COVID-19 pandemic. Nearly 28% of the national and 32% of the regional samples from the COVID Impact Survey were at risk for food insecurity. The logistic regressions show that chronically ill US adults with one of the following characteristics have higher odds of being at risk for food insecurity: younger than 60 years, having financial stress, unemployed, having received food from a food pantry, without health insurance, having a household income lower than 100,000, and without a college degree. Targeted policies and programs are warranted to address underlying determinants of food insecurity that adults with chronic illnesses experience.